PEDAGOGICAL CONDITIONS FOR DEVELOPING PRACTICAL SKILLS OF FUTURE ENGINEERS BASED ON PROGRAMMED EDUCATIONAL TOOLS - Sharipova Nodira Ilhom qizi (Western European Studies, 2025)
This article discusses the importance of programmed learning tools in preparing engineering students for practical work and the pedagogical conditions necessary for their effective use. Factors such as the integration of modern technologies in the educational process, interactive and contextual learning, and the new role of the teacher are important factors in improving the quality of engineering education. Engineering education plays a crucial role in addressing global technological and industrial challenges. In an era defined by rapid advancements in technology and increasing complexity in industrial systems, the demand for skilled engineers continues to rise.
Keywords: engineering education; programmed learning tools